Tinjauan Teori Critical Legal Studies Dalam Pandangan Mahasiswa Fakultas Syariah IAIN Ponorogo Terkait Pencegahan Money Politic Pemilu 2024 - Iriani, Dewi; Munawaoroh, Diana Nasiatul; Marvinda, Elsa Sintya (Institut Agama Islam Negeri Ponorogo, 2024)
Money politics is an act of dishonesty in a campaign that influences other people or the community by giving money or certain goods or you could say buying and selling votes when approaching the election, so that the community chooses a certain candidate. The formulation of the problem studied is 1) What is the role of IAIN Ponorogo students in guarding the prevention of money politics in the 2024 Election? 2) How can students' attitudes towards criticizing the occurrence of money politics in the implementation of the 2024 elections be studied using Critical Legal Studies theory? The research methodology uses qualitative methods, and the type of normative juridical research is in the form of Law No. 7 of 2017 concerning General Elections. The research approach uses 1) conceptual research using Critical Legal Studies theory as an analytical tool. 2) case study research, in the form of a case of money politics in the 2024 elections. 3) Sociology research, the author conducted interviews with Syariah faculty students at IAIN Ponorogo regarding money politics in the 2024 elections. The research results are: 1) The role of sharia faculty students at IAIN Ponorogo in guarding and preventing money politics in the 2024 Election, namely: providing education to the public, the BEM Chair Election was carried out transparently, honestly, without engaging in money politics. Providing understanding to the public, to choose the vision and mission of election candidates, not choosing because of money or gifts. Educate the public about the dangers of political money which is prohibited by religion, and get sanctions based on Article 515 of Law No. 7 of 2017 concerning Elections. Eliminate the cultural tradition of receiving money or gifts before elections. Select potential leaders with integrity. 2) Political money in the implementation of the 2024 elections, if studied using the Critical Legal Studies theory, that critical legal studies has characteristics, namely: political interests, groups of people who are not neutral, benefiting certain parties. detrimental to the general public